Grenada. Significant Achievements 2020 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2021)
The main activities carried out by the Institute in Grenada during 2020 are identified, with respect to the needs and interests of the country, in favor of agricultural innovation, gender equity, agricultural production and food security. Likewise, among the achievements carried out, the progress of the different projects implemented, the extension activities in the dissemination of information with publications, forums, training and research are recognized. Finally, for the recovery of the rural sector due to the post-COVID-19, two institutions that house vulnerable young people and battered women, benefited by the IICA Special COVID-19 Fund for the Caribbean Region.